Logic, Rationality, and Interaction 8th International Workshop, LORI 2021, Xi'an, China, October 16-18, 2021, Proceedings - Ghosh, Sujata; Icard, Thomas (Theoretical Computer Science and General Issues, 2021)
XIV, 289 p. 38 illus., 2 illus. in color.